Analisis terhadap Capaian Hasil Pembelajaran Akidah Akhlak terhadap Akhlak Siswa Sehari-hari - Suci Oktariani; Ahmad Kosasih (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The purpose of this study was to determine the achievement of the results of Akidah Akhlak learning on the daily morals of students through the syllabus indicators in the moral creed. This study uses descriptive qualitative research methods with the type of field research research type case study research. The data obtained using the technique of observation, interviews, questionnaires and documentation. The data analysis of this research includes the stages of data reduction, data presentation and conclusion drawing. The results of the study show that the achievement of the results of Akidah Akhlak Learning at Madrasah Tsanawiyah Negeri 12 Tanah Datar on Student Morals in accordance with the sub-indicators of the syllabus for Akhlaq subjects using the 2013 Revised Curriculum in the scope of achievements in the academic field, achievements in the field of aqidah and achievements in the field of morals.